Selected areas in cryptography 14th international workshop, SAC 2007, Ottawa, Canada, August 16-17, 2007 : revised selected papers - SAC (Conference) (Lecture notes in computer science, 2007)
SAC 2007 was the 14th in a series of annual workshops on Selected Areas in Cryptography. This is the ?rst time this workshop was held at the University of Ottawa. Previous workshops were held at Queen’s University in Kingston (1994, 1996, 1998, 1999, and 2005), Carleton University in Ottawa (1995, 1997, and 2003), University of Waterloo (2000 and 2004), Fields Institute in Toronto (2001), Memorial University of Newfoundland in St. Johns (2002), and Conc- dia University in Montreal (2006). The intent of the workshop is to provide a stimulating atmosphere where researchersin cryptology can present and discuss new work on selected areas of current interest. The themes for SAC 2007 were: – Design and analysis of symmetric key cryptosystems – Primitives for symmetric key cryptography, including block and stream ciphers, hash functions, and MAC algorithms – Eficient implementations of symmetric and public key algorithms – Innovative cryptographic defenses against malicious software A total of 73 papers were submitted to SAC 2007. Of these, one was wi- drawn by the authors, and 25 were accepted by the Program Committee for presentation at the workshop. In addition to these presentations, we were for- nate to have two invited speakers: – Dan Bernstein: “Edwards Coordinates for Elliptic Curves” – MotiYung:“CryptographyandVirologyInter-Relationships. ”Thistalkwas designated the Sta?ord Tavares Lecture. We are grateful to the Program Committee and the many external reviewers for their hard work and expertise in selecting the program. Reduced Complexity Attacks on the Alternating Step Generator -- Extended BDD-Based Cryptanalysis of Keystream Generators -- Two Trivial Attacks on Trivium -- Collisions for 70-Step SHA-1: On the Full Cost of Collision Search -- Cryptanalysis of the CRUSH Hash Function -- Improved Side-Channel Collision Attacks on AES -- Analysis of Countermeasures Against Access Driven Cache Attacks on AES -- Power Analysis for Secret Recovering and Reverse Engineering of Public Key Algorithms -- Koblitz Curves and Integer Equivalents of Frobenius Expansions -- Another Look at Square Roots (and Other Less Common Operations) in Fields of Even Characteristic -- Efficient Explicit Formulae for Genus 2 Hyperelliptic Curves over Prime Fields and Their Implementations -- Explicit Formulas for Efficient Multiplication in -- Linear Cryptanalysis of Non Binary Ciphers -- The Delicate Issues of Addition with Respect to XOR Differences -- MRHS Equation Systems -- A Fast Stream Cipher with Huge State Space and Quasigroup Filter for Software -- Cryptanalysis of White-Box DES Implementations with Arbitrary External Encodings -- Cryptanalysis of White Box DES Implementations -- Attacks on the ESA-PSS-04-151 MAC Scheme -- The Security of the Extended Codebook (XCB) Mode of Operation -- A Generic Method to Design Modes of Operation Beyond the Birthday Bound -- Passive–Only Key Recovery Attacks on RC4 -- Permutation After RC4 Key Scheduling Reveals the Secret Key -- Revisiting Correlation-Immunity in Filter Generators -- Distinguishing Attack Against TPypy.